Multi-level governance and social cohesion in the European Union: the assessment of local agents, a study case inside Galicia - López-Viso,Mónica (2014)
Implementing multi-level governance has been a key priority in EU cohesion policy. This study assesses the perceived achievements and shortcomings in implementing European Social Fund by analyzing the deficits and weaknesses as well as the poor participation of local agents who are in direct contact with the beneficiaries in order to design and implement this fund, which is the main financial instrument of EU social policy.